Research on anti-disturbance performance for servo system with a high dynamic performance velocity acquisition method. Issue 2 (June 2018) - Hua, Ji; Shuang, Wang
In order to achieve the requirements of high anti-disturbance and robustness performance for servo system, the acceleration control with disturbance observer is adopted in this paper, where the disturbance observer is used to estimate and compensate the load disturbance. To accomplish the accurate disturbance estimation, higher cut-off frequency of disturbance observer and exact acceleration information are required, where accurate speed estimation is crucial. Thus, a novel velocity acquisition method for servo control system with optical encoder is proposed. At the same time, dynamic error is put forward as a new performance metrics to scientifically explain the dynamic performance of this algorithm. The proposed velocity acquisition method is implemented based on a field programmable gate array. Experimental results show that this novel velocity acquisition method can improve dynamic response performance on the premise of guaranteeing the invariable velocity precision, and at the same time can effectively improve the anti-disturbance and robustness performance of the servo system.